IMPLEMENTATION OF THE PARAS VILLAGE FUND POLICY, CEPOGO DISTRICT, BOYOLALI REGENCY IN HANDLING CORONA VIRUS DISEASE (COVID 19) - Hadipuro, Razali; Supardal, Supardal (DIA: Jurnal Administrasi Publik, 2022)
Implementation of the Paras Village Fund Policy, Cepogo District, Boyolali Regency in Handling Corona Virus Disease (Covid 19), In Handling Covid-19. Thesis. Government Science Masters Program. STPMD "APMD’’ Yogyakarta High School for Village Development. The Village Fund is part of the village finances which is one of the priority Village incomes to finance development expenditures and empowerment of rural communities. This study uses a qualitative descriptive method, using interview techniques, documentation and observations of village officials and community leaders in Paras village in analyzing the Implementation of the Paras Village Fund Allocation Policy, Cepogo District, Boyolali Regency in Handling Corona Virus Disease (Covid 19). The results showed that the implementation of the Paras Village Fund was very good because it had the expertise, available budget, adequate facilities and had the authority to implement the village fund allocation policy. The disposition between the parties in the implementation of the village fund allocation policy has gone well because the policy implementers have good knowledge and understanding and have a high commitment in carrying out their duties. The bureaucratic structure in implementing the village fund allocation policy has served according to responsibilities, carrying out tasks in accordance with the provisions being carried out, where the division of work is in accordance with the main tasks and functions, coordination between sections is going well based on SOPs in implementation related to village fund allocation used. the implementation of the village fund allocation policy has gone well, which already has a clear information transformation with the socialization, and has consistency regarding the clarity of information on the implementation of the Village Fund